Anosmia in the first coronavirus disease 2019 outbreak in Europe: functional recovery after eight months. Issue 3 (26th March 2021) - Capelli, M; Gatti, P
Abstract: Background: Severe acute respiratory syndrome coronavirus-2 is a formidable virus, responsible for coronavirus disease 2019 and endowed with marked neurotropism. The damage it causes to the nervous system is manifold. The main neurological manifestation is anosmia. Olfactory damage is often transient, but there are no data reflecting an observational period of several months. Objective: This study evaluated the trend of anosmia in patients affected by coronavirus disease 2019 in the eight months following diagnosis. Methods: Fifty-five subjects who presented with symptoms suggestive of coronavirus disease 2019 and who developed anosmia, between the end of February and the beginning of March 2020, were investigated. The patients were interviewed after eight months to determine functional recovery and assess the degree of recovery. Results: Ninety-one per cent of the population reported olfactory recovery and, of these, 53 per cent had total recovery after eight months. Females and younger age groups seem slightly advantaged in functional recovery. The elderly population appears to have excellent prospects for full functional recovery. Conclusion: Anosmia represents a frequent neurological manifestation during coronavirus disease 2019. Fortunately, it is transient in most cases, and only a small percentage of patients affected by it report long-term functional deficits.